Нематеріальні активи підприємства: сучасний стан, деякі підходи до оцінки - Бриль, І.В.; Ревва, А.М. (Стратегія і механізми регулювання промислового розвитку, 2014)
Розглянуто питання економічної сутності нематеріальних активів, використання передових технологій та об’єктів права інтелектуальної власності, порівняльна динаміка показників інноваційної діяльності підприємств. Визначено сучасні підходи до оцінки нематеріальних активів на підприємстві. Розглянуто переваги й недоліки кожного з підходів до оцінки даного виду активів. Рассмотрены вопросы современного экономического состояния нематериальных активов, использования передовых технологий и объектов права интеллектуальной собственности, сравнительная динамика показателей инновационной деятельности предприятий. Определены современные подходы к оценке нематериальных активов на предприятии. Рассмотрены преимущества и недостатки каждого из подходов к оценке данного вида активов. The article deals with the economic substance of intangible assets, the use of advanced technology and intellectual property rights, comparative dynamics of innovation activity. Identified current approaches to valuing intangible assets in the enterprise. Advantages and disadvantages of each approach to the assessment of this type of asset.It is noted that all current existing evaluation methods are based on one of three classical approaches: income approach (determination of the potential return on assets); market approach (comparing the estimated object of close analogues, which were sold in the market); cost approach (setting the cost of acquisition of the asset).Determined optimal combination of these methods complement one another as the specifics valuation of intangible assets is virtually impossible to make their mark.